Fear Street : Trapped - Stine, R. L. (New York A Parachute Press Book, 1997)
There's an old story about something horrible happening in the tunnels under Shadyside High School, but exploring them seems more fun than Saturday detention until a group of kids find themselves up against something dark and evil and no longer human.
Keywords: Horror tales -- Schools